Improving The Capacity Of Managers Of Productive Wakaf Business Units Through Digital Marketing Training And Use Of Smart Cashier Applications - Ardiani, Ninda; M Ruslianor M; Satrio Sudarso (Amaluna: Jurnal Pengabdian Masyarakat, 2024)
Productive waqf own potential big in empowerment social and economic society, especially if managed optimally. Article This discuss implementation of community service programs society that aims increase capacity business unit manager endowment productive through training digital marketing and use Smart Cashier Application. Training covers management business based on POAC, digital marketing strategies, and utilization technology for efficiency operational. The results show existence improvement skills digital management and marketing, improvement turnover sales, as well as efficiency more operational​ Good through recording more transactions​ accurate. In addition, product branding is also strengthened for increase Power competitive in the market. This program succeed empowering manager business as well as create opportunity economy new for public around.